Karl Gustaf Torsten Sjögren and the Sjögren-Larsson syndrome - Khalid Al Aboud; Daifullah Al Aboud (Dermatology Reports, 2011)
Karl Gustaf Torsten Sjögren (1896-1974) a Swedish psychiatrist and geneticist, was a pioneer of modern Swedish psychiatry. Sjögren studied medicine at the University of Uppsala. From 1932 to 1935, he was Head Physician and Director of Lillehagen Hospital in Gothenburg, and between 1935- 1945, he was physician-in-chief at the psychiatric department of Sahlgrenska Hospital in Gothenburg. Sjögren was professor of psychiatry at Karolinska Institutet from 1945 to 1961 and was elected to the Royal Swedish Academy of Sciences in 1951. Sjögren was an expert of psychiatry for the World Health Organization. Among his many contributions to medicine, he is credited for describing several medical conditions, which were later named after him, including Graefe- Sjögren syndrome, Marinesco-Sjögren syndrome, and Sjögren-Larsson syndrome (SLS). During his work on juvenile amaurotic idiocy, Sjögren forged a collaboration with Tage K.L. Larsson, a statistics lecturer at the University of Lund. Their study on the combination of oligophrenia, congenital ichthyosis, and spastic disorders in 1957 established the clinical and genetic profile of a new disease entity, later known as Sjogren-Larsson syndrome (SLS).